Hubungan Konsep Diri terhadap Kepercayaan Diri Siswa Kelas XII SMA Teuku Umar Semarang - Ariyani, Selgi Mei; Handayani, Arri; Setiawan, Agus (Faculty of Teacher Training and Education of Undaris, 2023)
Research on the Relationship between Self-Concept and Self-Confidence in Class XII Students of Teuku Umar High School, Semarang motivated by the lack of self-confidence of class XII students, this is indicated by the results of the AKPD (Students Needs Questionnaire) many students still chose the item